The Subtitle Strategy of Cultural Translation in “Murder on The Orient Express” Movie - Wiwin Rosari Saragih; Elisa Betty Manullang (TRANSFORM : Journal of English Language Teaching and Learning, 2022)
This research examines the translation strategies used in movie subtitles and their relation to the cultural context. The translation of subtitles on movie is strongly influenced by grammar and culture. To get the right meaning, a translation strategy is needed in translating subtitles on movie that can adjust the cultural context from the source language to the target language. This study aims to find out the subtitle strategy applied in translating the movie subtitle "Murder On The Orient Express" related to culture and to clarify the reason subtitle strategy that related to culture context occur in the movie subtitle. This research was conducted using a qualitative descriptive method. The data found in this study were 563 data. The results showed that there were 7 translation strategies related to cultural context that were applied to the translation of the subtitle "Murder On The Orient Express" movie. They were direct translation found 269 times, generalization used 100 times, substitution used 76 times, retention used 49 times, specification used 43 times, omission used 25 times and official equivalent used 1 time. The subtitles in this movie contain cultural bound terms and the grammatical structure of the language used by the actors is influenced by their respective cultures. Therefore, the subtitle strategy related to the cultural context occurs in the subtitle of this movie. Appropriate translation strategies must be applied to achieve equivalence of meaning from the source language to the target language.